PENGARUH KARAKTERISTIK PEKERJAAN, SEMANGAT KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN KEPEGAWAIAN DAN PEMBERDAYAAN SUMBERDAYA MANUSIA KABUPATEN KOLAKA TIMUR - Runda, Rismanto; Muthalib, Abd. Azis; Sabilalo, Mahmudin A. (JISEF : Journal Of International Sharia Economics And Financial, 2024)
This study aims to determine and analyze the influence of job characteristics, work enthusiasm, and work ability on employee performance at the Office of Personnel and Human Resource Empowerment of East Kolaka Regency. The sample in this study consisted of all employees at the Office of Personnel and Human Resource Empowerment of East Kolaka Regency, totaling 46 individuals. This study uses PLS analysis. The results of the study show that: (1) Job characteristics have a positive and significant effect on employee performance at the Office of Personnel and Human Resource Empowerment of East Kolaka Regency. (2) Work enthusiasm has a positive and significant effect on employee performance at the Office of Personnel and Human Resource Empowerment of East Kolaka Regency. (3) Work ability has a positive and significant effect on employee performance at the Office of Personnel and Human Resource Empowerment of East Kolaka Regency.